Unraveling genetic etiologies in complex pediatric neurological diseases: A genetic investigation using whole exome sequencing - Zainab Gaouzi; Aziza Belkhayat; Zahra Chebihi Takki; Hind Lachraf; Idrissa Diawara; Yamna Kriouile (PLoS ONE, 2025)
Pediatric neurological disorders are a diverse group of conditions affecting the nervous system in children, often challenging to diagnose due to their nonspecific and overlapping clinical features. Advances in molecular diagnostics, particularly whole exome sequencing (WES), have significantly improved the identification of genetic causes, enabling precise diagnoses and personalized treatments. This study explores the application of WES in diagnosing pediatric neurological disorders within Moroccan childrens with undiagnosed or challenging pediatric neurological conditions to uncover genetic causes of complex pediatric neurological conditions unresolvable by traditional diagnostic methods. The study included 188 pediatric patients with complex neurological conditions from the Children’s Hospital of Rabat who underwent exome sequencing to investigate suspected genetic causes. WES revealed a diagnostic yield of 45%, identifying conditions such as intellectual disabilities, hereditary metabolic disorders and epilepsies. It also uncovered neurodevelopmental and neurodegenerative disorders, neuromuscular diseases, and genetic syndromes. A total of 157 variants were detected: 34% were classified as pathogenic, 28.5% as likely pathogenic, and 37.5% as variants of uncertain significance (VUS). These findings underscore the utility of WES as a robust diagnostic tool, providing insights into genetic causes and enabling tailored treatment strategies. They also highlight the importance of expanding genetic research to improve diagnostic accuracy and clinical management of pediatric neurological disorders.